the difficult balance between the dignity of the fetus and the self-determination of the woman: normative analysis of the burial of fetuses in the american and italian realities (TEST BioLaw Journal - Rivista di BioDiritto, 2023)
This paper, through the analysis of Italian legislation and U.S. jurisprudence on the subject of the burial of aborted fetuses, aims to highlight the effects of the imposition of legal obligations in this matter on women’s constitutionally guaranteed rights to freedom of conscience, religion and choice. The experiences analyzed highlight how the disciplines introduced in order to protect the dignity of the conceived stand as an obstacle, as much to access to the abortion practice, as to the full self-determination of the woman.
Keywords: Burial; aborted fetuses; mortuary regulations; special waste disposal; self-determination